Epidemiological characteristics and genotype distribution of human papillomavirus infection in Yangpu district, Shanghai, 2020–2024 - Zien Cheng; Yu Zhao; Ting Xu; Liting Wu; Hongdan Zhao; Jia Li (Virology Journal)
Abstract Objective To analyze the positive rate and genotype distribution of human papillomavirus (HPV) infection in Yangpu District, Shanghai, and to provide a scientific basis for the prevention and treatment of cervical cancer and related diseases. Methods A retrospective analysis was conducted on HPV genotyping data from 19,142 outpatients, inpatients, and health examinees at Shanghai Shidong Hospital from 2020 to 2024. Overall infection rate, genotype distribution, age-specific positivity, and annual trends were evaluated. Results Among 19,142 specimens, 4,421 tested positive for HPV, yielding a total positive rate of 23.10%. The top five prevalent genotypes were HPV-52 (21.72%), HPV-53 (11.94%), HPV-58 (10.19%), HPV-51 (8.02%), and HPV-39 (6.86%). Dominant genotypes varied across years. Age-specific infection rates followed an approximate U-shaped curve, with peaks in the ≤ 20-year group (57.69%) and the 61–70-year group (29.72%). Among mixed infections (28.70% of positives), single infections predominated (71.30%). The most common co-infection combinations were HPV-52 + HPV-53 and HPV-52 + HPV-58. High-risk age groups for HPV infection were 31–40, 51–60, and 61–70 years. Conclusion The HPV infection rate in Yangpu District, Shanghai, was 23.10%, primarily driven by single-genotype infections. HPV-52, -53, and − 58 were the dominant genotypes, with significant age-specific variations. These findings underscore the need for enhanced HPV vaccination promotion and targeted preventive strategies.